2016
DOI: 10.1097/brs.0000000000001706
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Cervical Laminoplasty and Postoperative Radiological Change for Cervical Myelopathy With Degenerative Spondylolisthesis

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…Similar findings were found in previous studies [3,46,47]. With regard to cervical spondylolisthesis, the overall prevalence has been reported previously to be 3.9-28.2%, and was mostly found at C4/C5 [35,36,39,[48][49][50]; the prevalence of anterior spondylolisthesis ranged from 0.9 to 6.3%, and of posterior spondylolisthesis from 0 to 13.3% [35-39, 49, 50]. Similarly, the current results showed that the overall prevalence of cervical spondylolisthesis was 6.5% (also mostly found at C4/C5); the prevalence of anterior and posterior spondylolisthesis was 2.5 and 3.9%, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar findings were found in previous studies [3,46,47]. With regard to cervical spondylolisthesis, the overall prevalence has been reported previously to be 3.9-28.2%, and was mostly found at C4/C5 [35,36,39,[48][49][50]; the prevalence of anterior spondylolisthesis ranged from 0.9 to 6.3%, and of posterior spondylolisthesis from 0 to 13.3% [35-39, 49, 50]. Similarly, the current results showed that the overall prevalence of cervical spondylolisthesis was 6.5% (also mostly found at C4/C5); the prevalence of anterior and posterior spondylolisthesis was 2.5 and 3.9%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Spondylolisthesis (anterolisthesis and retrolisthesis) was noted as ''present'' or "absent" for each subject and intervertebral disc level and was defined as 2 mm or more vertebra slippage of the cranial vertebra on the caudal vertebra in the anterior or posterior direction [30][31][32][33][34][35][36][37]. The slippage distance was measured from the poster inferior corner of the cranial vertebra to the tangential line along the posterior border of the caudal vertebra.…”
Section: Radiographic Assessmentmentioning
confidence: 99%
“…Recent years, studies show that because of the characteristics of large activity and poor stability of cervical vertebrae, there are bone graft loss and collapse induced cervical deformity, pseudoarthrosis and other complications during the anterior cervical decompression and bone graft fusion [7]. Also long time external fixations are required postoperative, for early break achievement and for better lateral intervertebral fusion [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…For decades, single-door cervical laminoplasty (SDCL) has developed to be the primary treatment for syndromes such as ossification of the posterior longitudinal ligament (OPLL), multilevel cervical spondylotic myelopathy (CSM), or multilevel cervical disc herniation associated with developmental spinal canal stenosis. [ 1 3 ] Compared to laminectomy, which dominated the surgery treatment for those syndromes before SDCL, SDCL creates more satisfying feedback from patients. Also, SDCL is much more straightforward and convenient for surgery operation.…”
Section: Introductionmentioning
confidence: 99%